Design and Development of a Competency Certificate Surveillance System for Electrical Technical Personnel using a Disruptive RSM Design Approach - Rika Mulyati; Muharman Lubis; Sinung Suakanto; A. Taupik Rahman (Universitas Dharma Wacana, 2025)
The competency certificate for electrical technical personnel serves as formal evidence that an individual is qualified to work in the electricity sector and has a validity period of three years, requiring periodic surveillance to ensure regulatory compliance. In practice, the surveillance process is still largely conducted manually by Competency Certification Bodies (LSK), resulting in administrative inefficiencies, delays in certificate renewal, fragmented documentation, and limited traceability of surveillance records. These challenges not only burden certification bodies and certificate holders but also affect regulatory supervision performance. This study aims to design and develop a competency certificate surveillance information system for electrical technical personnel using a disruptive Recognise–Scrutinize–Materialize (RSM) design approach. Data were collected through observations, semi-structured interviews, and document analysis to identify existing problems and system requirements. The RSM method was applied to systematically align stakeholder needs with national regulations and international standards, including ISO, IEEE, and NIST guidelines. The results of this research produce a regulation-based surveillance system design in the form of a structured mock-up that integrates automated reminders, digital document validation, standardized surveillance workflows, and real-time monitoring dashboards. The proposed system is expected to improve efficiency, data accuracy, transparency, and regulatory compliance in the surveillance and renewal process of competency certificates. This research contributes novel insights into the digitalization of competency certificate surveillance, a topic that has received limited attention in previous studies, particularly within the electricity sector.